(untitled) (Bangladesh Journal of Zoology, 2021)
The study was conducted to understand the occurrence of gastrointestinal parasites in horse during June, 2017 to April, 2018 from Bangladesh National Zoo, Puran Dhaka and Rajarbagh Police Line of Dhaka city. A total of 48 faecal samples were collected from horses and examined by Direct Smearing technique and Formol Ether Concentration technique. Out of 48 samples 47 found positive for gastrointestinal parasitic infection with an overall prevalence of 97.92 %. Highest prevalence was identified (77.1 %) in Parascaris equorum, followed by 70.8 % in Hymenolepis nana, 62.5 % in Isospora sp., 50 % in Ancylostoma duodenale, 39.6 % in Toxocara sp., 35.4 % in Entamoeba sp., 25 % in Trichuris sp., 20.8 % in Fasciola hepatica 16.67 % in Capillaria sp., 8.3 % in Taenia sp. and Opisthorchis sinensis, 4.2 % in Moniezia benedeni and Thysaniezia sp. Highest intensity (72.97± 46.32) was found for Isospora sp. The p value was 0.01, p < 0.05 so the prevalence rate was statistically significant.A significant difference was founded in prevalence between male and female horse where females were highly infected and also seasonal variation showed significant differences. Highest prevalence was recorded in winter and Rainy season (100 %) followed by summer (95 %). The intensity of parasites was highest in rainy season (63.38 ±79.94) followed by summer (55.47 ±29.73) and winter (49.5 ±28.58) Bangladesh J. Zool. 49 (2): 301-319, 2021